Deficit mulched drip irrigation improved yield and quality while reduced water consumption of isatis indigotica in a cold and arid environment - Zhou, Chenli; Zhang, Hengjia; Li, Fuqiang; Wang, Yong; Wang, Yucai; Wang, Zeyi (Frontiers in Plant Science, 2022)
Deficit irrigation is an effective alternative to traditional irrigation, as it improves crop productivity and conserves water. However, crops may be sensitive to deficit irrigation-induced water stress at different periods. To access the effect of deficit irrigation on the growth, water consumption characteristics, yield, and quality of Isatis indigotica, we performed a three-year (2017-2019) mulched drip irrigation field experiment. I. indigotica plants were provided adequate water supply at the seedling stage but were subjected to mild, moderate, and severe water deficit at the other stages, respectively; plants supplied with adequate water throughout the growth period served as a control (CK). The water consumption characteristics, agronomic traits, dry matter content and distribution, yield, and quality of these plants were measured at various growth stages. The results showed that the total water consumption in water deficit was significantly less than that in CK by 4.44–10.21% (P < 0.05). The dry matter content of plants treated with moderate and severe water deficit was reduced by 12.83–28.75%, while the dry matter content of plants treated with mild water deficit showed no significant difference. The economic yield of mild water deficit-treated plants was higher during vegetative growth and fleshy root growth, while the water use efficiency of these plants was significantly increased by 7.84% and 6.92% at the two growth stages, respectively. Continuous mild water deficit enhanced the contents of indigo, indirubin, (R,S)-goitrin, polysaccharides, and soluble proteins during vegetative growth and fleshy root growth, while moderate and severe water deficit were detrimental to the quality of I. indigotica plants. Thus, continuous mild water deficit during vegetative and fleshy root growth periods is optimal for the cultivation of I. indigotica in the cold and cool irrigation district of the Hexi Oasis region.